2017
DOI: 10.1186/s12957-017-1217-1
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal cancer in a patient with intestinal schistosomiasis: a case report from Kilimanjaro Christian Medical Center Northern Zone Tanzania

Abstract: BackgroundColorectal cancer associated with chronic intestinal schistosomiasis has been linked with the chronic inflammation as a result of schistosomal ova deposition in the submucosal layer of the intestine. Among all species Schistosoma japonicum has been more linked to development of colorectal cancer as compared to Schistosoma mansoni due to absence of population-based studies to support the association. Despite the weak evidence, some cases have been reported associating S. mansoni with development of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“…In non-endemic regions with individuals immigrating from affected countries, some guidelines suggested screening for schistosomiasis as a way of improving identification of infected patients, increase treatment rates, and ultimately reduce any complications of disease progression [ 7 , 8 ]. Previous studies have found high rates of active schistosomiasis in immigrants from Schistosoma endemic regions, therefore screening this population with serology and ELISA testing may be effective [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In non-endemic regions with individuals immigrating from affected countries, some guidelines suggested screening for schistosomiasis as a way of improving identification of infected patients, increase treatment rates, and ultimately reduce any complications of disease progression [ 7 , 8 ]. Previous studies have found high rates of active schistosomiasis in immigrants from Schistosoma endemic regions, therefore screening this population with serology and ELISA testing may be effective [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“… Diverting transverse colostomy was deemed the safest treatment by consensus. Herman et al (2017) [ 8 ] 52; M Tanzania 4d history of abdo. pain, distension, and constipation.…”
Section: Discussionmentioning
confidence: 99%
“…The association between schistosomiasis and CRC has been determined previously (9) and large epidemiological studies have demonstrated an association between CRC and schistosomiasis (10,11). Several studies have suggested that long-term inflammation caused by chronic schistosomal infection is a key factor in the carcinogenic process of CRC (12,13). However, there are only a few studies which have reported differences in the characteristics between patients with schistosomal and nonschistosomal CRC and the number of reported schistosomal CRC cases is low (14,15).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, poor sanitation, bathing and swimming in dams and rivers or crossing rivers on the way to school barefooted, type and consistent use of toilet, uses of unprotected water sources to watering the vegetable gardens and knowledge about schistosomiasis are the risks that significantly associated with higher rates of infection [ 16 ]. The adverse effects of schistosomiasis among this group are diverse and alarming, the infection can lead to urethral and bladder fibrosis and hydronephrosis, hepatosplenomegaly, moreover, bladder cancer and colorectal cancer is a possible late-stage complication [ 17 , 18 ]. Thus, this study was conducted to determine the prevalence of schistosomiasis and the associated risk factors among school age children from Um-Asher area, South Khartoum, Sudan.…”
Section: Introductionmentioning
confidence: 99%